Bavaria's Supreme Court - Manfred Dauster (Bratislava Law Review, 2022)
Courts shape the rule of law. Their history is part of the culture of a country. The way judicial institutions are treated characterises a country's attitude towards the status they accord to courts and judges. In its almost 400-year history, Bavaria's Supreme Court has experienced all facets - from being held in high esteem to being abolished twice. Its history is a lesson that points to the future in the development of European legal culture.